Wind turbine lightning protection receptor with sharp needles - Wahdain, S. S.; Amir Izzani, Mohamed; Mohd Herwan, Sulaiman; Ahmad Salihin, Samsudin; Rahisham, Abd Rahman (IEEE, 2024)
Wind turbines, as a form of renewable energy, are often located in remote, open areas such as offshore locations, mountainous regions, and deserts, where they are susceptible to lightning strikes. The blades of a wind turbine are susceptible to damage from lightning strikes due to their large size and position as the highest point in the wind turbine structure. Previous research focused on the size and location of receptors. Despite implementing a lightning protection system, it is not always effective in preventing lightning strikes on a wind turbine. Instead, other parts of the turbine may be struck, resulting in catastrophic damage to the equipment. From a technical perspective, using sharp needles as part of a lightning protection system can act as a lightning rod, drawing the electrical charge from a lightning strike and redirecting it away from the equipment, thus decreasing the potential for damage to the structure. Use 0.2m receptor size with two different numbers of needles, 16 and 32. The result obtained using the Finite Element Method showed a good result compared to the receptor without needles. It was observed through modelling that, when utilizing a receptor with 32 needles, the electric field measured was 3.69 MV/m, whereas when using a receptor with 16 needles, the electric field measured was 2.2 MV/m.